2007
DOI: 10.1111/j.1439-0310.2007.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoaling Decisions in Angelfish: The Roles of Social Status and Familiarity

Abstract: Past research has shown that angelfish, Pterophyllum scalare, are capable of discriminating between shoals composed of familiar dominant and subordinate companions, whereas they show no preference for shoals of unfamiliar conspecifics. In this study, the relative importance of familiarity and social status (shoal factors) on the shoaling decision of juvenile angelfish, which also differed in social status (individual factor), was investigated as very little is known about such tradeoffs in fishes. Dominant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
8
0
3
Order By: Relevance
“…When given a choice between familiar and unfamiliar dominant conspecifics, the subordinate angelfish preferred to associate with the unfamiliar fish. Dominant fish exposed to the same test did not demonstrate any clear preference (Gomez-Laplaza & Fuente 2007). Similar results were reported in the humbug damselfish (Dascyllus aruanus) where subordinate individuals are choosier than dominant fish (Jordan et al 2010).…”
Section: Functions Of Associating With Familiar Fishsupporting
confidence: 82%
“…When given a choice between familiar and unfamiliar dominant conspecifics, the subordinate angelfish preferred to associate with the unfamiliar fish. Dominant fish exposed to the same test did not demonstrate any clear preference (Gomez-Laplaza & Fuente 2007). Similar results were reported in the humbug damselfish (Dascyllus aruanus) where subordinate individuals are choosier than dominant fish (Jordan et al 2010).…”
Section: Functions Of Associating With Familiar Fishsupporting
confidence: 82%
“…The precise mechanisms behind the behavioural biases observed in this study are not known. In viviparous fishes such as embiotocids, it is difficult to completely separate the role of familiarity from other factors because live‐bearing fishes can become familiar with each other before and immediately after birth, and familiarity per se has been shown to influence shoaling preferences in a variety of fishes (Van Havre & Fitzgerald, 1988; Dugatkin & Wilson, 1992; Hojesjo et al , 1998; Barber & Wright, 2001; Gomez‐Laplaza & Fuente, 2007). Magurran et al (1995) found that free‐living juvenile guppies Poecilia reticulata Peters, the only other live‐bearing fish studied to date, were more closely related than the average for the population.…”
Section: Discussionmentioning
confidence: 99%
“…P. reticulata : Griffiths & Magurran, 1998; Godin et al , 2003). Moreover, some fish species have no preference for familiar shoalmates or there are even situations where familiar shoalmates are actively avoided (Frommen et al , 2007; Gómez‐Laplaza & Fuente, 2007). Whether familiarity occurs through individual or general group recognition, or even via a chemical cue preference for fishes occupying the same habitat or sharing a similar diet, is an important question that has been addressed in fishes only recently (Ward et al , 2004, 2005; Webster et al , 2007).…”
Section: Introductionmentioning
confidence: 99%